Strategic Leadership as a Contemporary Trend in Educational Institutions: An Analytical Study of the Concept, Dimensions, and Challenges in the Kingdom of Saudi Arabia - Al-Shahri, Sarah Ajlan (Journal of Educational and Psychological Sciences, 2025)
This study aimed to clarify the concept, dimensions, and challenges of Strategic Leadership (SL) as a modern trend in educational institutions within the Kingdom of Saudi Arabia (KSA), and to identify its strengths and areas needing improvement. The study employed the descriptive-analytical approach through a systematic review of specialized literature related to educational management and leadership, utilizing content analysis as the primary research tool. Findings indicated that SL is based on core dimensions, including clarity of strategic vision and mission, building and developing human capital, cultivating a supportive organizational culture, effective use of data in decision-making, and commitment to ethical practices and good governance. The study also revealed several key challenges hindering its field application, most notably: the persistence of a traditional administrative style, weak empowerment of educational leaders, a deficit in leader preparation programs focusing on strategic competencies, limited resources, and the clear absence of metrics for evaluating strategic leadership performance. Based on these findings, the study presented a proposed conceptual framework for activating this leadership style in light of accelerating environmental shifts. It recommended redesigning educational leader preparation programs to include SL components, such as future thinking and change management, empowering field leadership by enhancing their administrative and organizational authorities, and suggesting the design of localized SL models that consider the realistic challenges and opportunities within KSA's educational institutions.
Keywords: Strategic Leadership; Dimensions of Strategic Leadership; Strategic Leadership in Educational Institutions; Challenges of Strategic Leadership